IMPROVEMENT OF FEEDING PRACTICES FOR STUNTING CHILDREN UNDER TWO YEARS THROUGH AN COMPLEMENTARY FEEDING EDUCATION - Erna Julianti; Elni; Restu Amalia Azmy (Nurse and Health: Jurnal Keperawatan, 2023)
Background: Feeding practice is one of the factors determining the stunting prevalence. It happens because the children’s food intake strongly depends on the feeding practice done by their parents. The role of parents would determine children's nutritional intake, in which inappropriate nutritional intake lead to stunting. Objectives: The aim of the study was to identify differences in the feeding practices of mothers to stunting children under two years before and after being given a complementary feeding intervention Methods: This is a quantitative study with a quasi-experimental one group design. The samples in this study were 31 respondents selected using the consecutive sampling technique. The inclusion criteria were mothers who have children aged 6-24 months with stunting (z score PB/U is less than -2SD). Exclusion criteria were that the mother or child was sick and did not receive complete intervention. Instrument used was a standard Comprehensive Feeding Practice Questionnaire (CFPQ) instrument. The intervention provided was in the form of education using audiovisual media and a demonstration of the practice of making complementary feeding. The analysis in this research is paired T test. Results: The average score on feeding practice for stunting Children Under Two Years after the nutrition intervention is higher, namely 112.32 compared to the average score on feeding practice for stunting Children Under Two Years before the nutrition intervention, namely 87.06. The results of the analysis found that there is a significant difference between the average score on feeding practice for stunting Children Under Two Years before and after the complementary feeding with p-value of 0.0001. Conclusion: The complementary feeding intervention can encourage the feeding practice of stunted under-two-year-old children.